Beyond biomedical and comorbidity approaches: Exploring associations between affinity group membership, health and health seeking behaviour among MSM/MSW in Nairobi, Kenya. Issue 7 (2nd July 2020) - Doshi, Monika; Macharia, Pascal; Mathenge, John; Musyoki, Helgar; Amico, K. Rivet; Battacharjee, Parinita; Blanchard, James; Reza-Paul, Sushena; McKinnon, Lyle R.; Kimani, Joshua; Lorway, Robert R.
ABSTRACT: We explored general health and psychosocial characteristics among male sex workers and other men who have sex with men in Nairobi, Kenya. A total of 595 MSM/MSW were recruited into the study. We assessed group differences among those who self-reported HIV positive (SR-HIVP) and those who self-reported HIV negative (SR-HIVN) and by affinity group membership. Quality of life among SR-HIVP participants was significantly worse compared to SR-HIVN participants. Independent of HIV status and affinity group membership, participants reported high levels of hazardous alcohol use, harmful substance use, recent trauma and childhood abuse. The overall sample exhibited higher prevalence of moderate to severe depressive symptoms compared to the general population. Quality of life among participants who did not report affinity group membership (AGN) was significantly worse compared to participants who reported affinity group membership (AGP). AGN participants also reported significantly lower levels of social support. Membership in affinity groups was found to influence health seeking behaviour. Our findings suggest that we need to expand the mainstay biomedical and comorbidity focused research currently associated with MSM/MSW. Moreover, there are benefits to being part of MSM/MSW organisations and these organisations can potentially play a vital role in the health and well-being of MSM/MSW.